The Prevalence of S. Mutans and Other Oral Streptococci in Dental Plaque and Saliva of Adults (Mustansiria Dental Journal, 2018)
Oral streptococci constitute the most oral bacterial groups in the human oral cavity. Most of the oral streptococci belong to the viridians group and include the species S. mutans, S. sanguis, S. salivarius and S. milleri.Dental plaques and saliva samples were randomly taken from 210 selected students of Education College of 22 – 24 years old. The results showed that S. mutans was isolated from 75 salivary samples (35.7%) and from 80 plaque samples (38.1%): the other oral streptococci were isolated from all saliva and plaque samples.